C (at) SiOx / MoSe2 (at) CS material synthesized based on waste plastic derived carbon as well as preparation method and application of C (at) SiOx / MoSe2 (at) CS material
By preparing C@SiOx/MoSe2@CS composite material, the limitations of existing sodium ion battery graphite anode materials are solved, and high-efficiency and low-cost sodium ion battery anode materials are achieved, with good cycle stability and electrochemical properties.
Patent Information
- Application Number
- CN202510697325.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-28
- Publication Date
- 2025-08-29
AI Technical Summary
The existing graphite anode materials for lithium-ion batteries are limited in application due to the large radius of sodium ions. Graphene and carbon nanotubes are costly, easy to agglomerate, and many hard carbon surface defects, resulting in low efficiency for the first time in sodium ion batteries and difficult to produce on a large scale.
The solution of waste plastic-derived carbon and Si-Mo organometallic compound is calcined under an inert atmosphere to form a three-layer heterobonding composite material. The carbon nanospheres and MoSe2 nanosheet structure formed by plastic pyrolysis are used to provide active sites and stable frameworks to avoid the increase in the thickness of the SEI film.
High cycle stability and excellent electrochemical performance are achieved. The discharge specific capacity of 387.53mAh g-1 after cycling 3000 times at 5Ag-1 is still 355.64mAh g-1 after 5000 times, which is low cost and easy to produce on a large scale.
Smart Images

Figure CN120553718A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrode materials, and in particular to a C@SiO2 composite based on waste plastic-derived carbon. x / MoSe2@CS material, its preparation method and application. Background Art
[0002] With the ever-increasing demand for electronic products and the emergence of a wide variety of portable electronic devices, lithium resources are being rapidly consumed and their supply is becoming increasingly tight. Considering energy storage capacity, researchers have turned their attention to sodium, an element in the same family as lithium. Although sodium and lithium are both alkali metals with similar chemical properties, and sodium is abundant and inexpensive, making it a potential alternative to lithium, the larger radius of sodium ions limits their use in existing graphite anodes in lithium-ion batteries.
[0003] Carbon materials, including graphene, carbon nanotubes, and hard carbon, have been widely studied as carriers and carbon sources for sodium-ion battery anodes due to their excellent conductivity and high surface area. While graphene and carbon nanotubes possess high conductivity and mechanical strength as carbon sources, they suffer from significant drawbacks: their complex and costly preparation processes make them difficult to scale up. Graphene's stacking reduces interlayer spacing, restricting sodium ion diffusion, while carbon nanotubes easily aggregate, reducing their effective specific surface area. Furthermore, both materials have numerous surface defects and oxygen-containing groups, resulting in low initial coulombic efficiencies and requiring additional modification, further complicating their application. Hard carbon, on the other hand, is considered an excellent candidate for sodium-ion battery anodes due to its high sodium capacity, low redox potential, good structural stability, and relatively low cost. Importantly, hard carbon is readily available from a wide range of raw materials and can be prepared from a variety of waste polymers, including polyethylene (PE), polypropylene (PP), and polystyrene (PS), enhancing its practicality while significantly reducing production costs.
[0004] Therefore, using abundant plastic waste on Earth as a precursor to prepare low-cost hard carbon has broad prospects. Summary of the Invention
[0005] In view of the shortcomings of the prior art, the present invention aims to provide a C@SiO2 composite material synthesized from waste plastics derived carbon. x / MoSe2@CS material, its preparation method and application.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In the first aspect, the present invention provides a C@SiO2 synthesized from waste plastic-derived carbon. x The preparation method of / MoSe2@CS material includes the following steps:
[0008] S1. Preparation of Si-Mo organometallic compound solution
[0009] Molybdenum pentachloride is dissolved in ethylene glycol solution A, and then triphenylsilyl chloride and ethylene glycol solution B are added to obtain a Si-Mo organometallic compound solution.
[0010] In this step, the molar ratio of molybdenum pentachloride to triphenylsilane is 1:1-5. In some embodiments of the present invention, for example, 1:1, 1:2, 1:3, 1:4, or 1:5 can be selected, but the ratio is not limited to the listed values. Other values not listed within the numerical range are also applicable.
[0011] In this step, the usage ratio of molybdenum pentachloride and ethylene glycol solution A is 25-30 mg:5-6 mL, for example, 25 mg:5 mL, 26.4 mg:5.3 mL, 27.2 mg:5.6 mL, 30 mg:6 mL can be selected, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0012] In this step, the volume ratio of ethylene glycol solution A to ethylene glycol solution B is 1:3-5, for example, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 can be selected, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0013] S2. Preparation of mixture
[0014] The discarded mask protective layer is added to the Si-Mo organometallic compound solution, and the mixture is evenly mixed to obtain a mixture.
[0015] In this step, the material of the protective layer of the discarded mask is polypropylene (PP).
[0016] In the technical solution provided by the present invention, the protective layer of the discarded mask is cut into pieces and then added to the Si-Mo organometallic compound solution.
[0017] S3. Preparation of C@SiO x / MoSe2@CS material
[0018] The above mixture was poured into a ceramic ark filled with selenium powder, and the ceramic ark was placed in a tube furnace and calcined under an inert atmosphere to obtain C@SiO x / MoSe2@CS material.
[0019] In the technical solution disclosed in the present invention, the mass ratio of molybdenum pentachloride, the protective layer of discarded masks and selenium is 1:10-30:0.5-2. For example, 1:10:0.5, 1:10:1, 1:10:2, 1:15:0.5, 1:15:1, 1:15:2, 1:20:0.5, 1:20:1, 1:20:2, 1:30:0.5, 1:30:1, 1:30:1.5, and 1:30:2 can be selected, but the values are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0020] In the technical solution disclosed in the present invention, the inert atmosphere is nitrogen or argon.
[0021] In the technical solution disclosed in the present invention, the calcination temperature is 750-900°C, for example, 750°C, 780°C, 800°C, 820°C, 850°C, 860°C, 880°C, 890°C, and 900°C can be selected; the calcination time is 1-2h, for example, 1h, 1.5h, and 2h can be selected; the heating rate is 5-10°C / min, for example, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, and 10°C / min can be selected, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0022] In the technical solution disclosed in the present invention, C@SiO x SiO in MoSe2@CS material x The x is 1 and / or 2.
[0023] The present invention uses waste masks with PP as the main protective layer as the carrier and carbon source, and calcines them with Si-Mo organometallic compounds to form a spherical composite material C@SiO x / MoSe2@CS, in which the protective layer PP is calcined to form a large number of nano-scale carbon spheres (CS), which are MoSe2 and SiO x The growth of MoSe2 nanosheets provides a large number of active sites, and the MoSe2 nanosheets grow along the surface of the carbon spheres. The uniformly dispersed MoSe2 nanosheets provide a large sodium storage capacity and a large amount of SiO x Particle dispersion sites, forming SiO x / MoSe2@CS composite material, coupled with an amorphous carbon coating formed by carbonization of organic matter, serves as a strong framework to cope with the SiO x / MoSe2@CS volume expansion and avoid the formation of thick SEI film. x / MoSe2@CS composite materials can be used as negative electrode materials for sodium ion batteries.
[0024] In the second aspect, the present invention provides C@SiO prepared by the above preparation method based on waste plastic-derived carbon synthesis x / MoSe2@CS material.
[0025] In a third aspect, the present invention also provides the C@SiO synthesized based on waste plastic-derived carbon. x Application of / MoSe2@CS materials in electrode materials.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention uses molybdenum pentachloride, triphenylchlorosilane, selenium, discarded mask protective layer PP, and ethylene glycol as raw materials and obtains C@SiO by calcination. x / MoSe2@CS three-layer heterojunction composite material, this three-layer material has a stable structure, good cycle stability and excellent electrochemical performance. -1 After 3000 cycles at a high current density, there is still 387.53 mA hg -1 The discharge capacity is 355.64mA hg after 5000 cycles. -1 discharge capacity.
[0028] (2) Compared with the prior art, the method provided by the present invention has the characteristics of simple method, easy availability of raw materials and low cost, which is conducive to the realization of its large-scale production.
[0029] (3) The present invention uses waste plastic derived carbon to replace carbon nanotubes, which can significantly improve the C@SiO x The electrochemical performance of MoSe2@CS materials is mainly due to the essential differences in microstructure and interface properties between the two. Carbon nanospheres formed by plastic pyrolysis have better stress buffering capacity than carbon nanotubes and can effectively adapt to the stress of SiO2. x The volume change during the charge and discharge process prevents the electrode structure from pulverizing. At the same time, this derivative carbon contains rich heteroatoms and defect sites, forming stronger chemical bonds with the active material and enhancing the interface stability. Compared with the CNT-based material in the patent application (application number 202411047170.5) previously applied by our research group, the plastic-derived carbon-based electrode can still maintain 355.64mA hg after 5000 cycles. -1 It has a larger capacity and exhibits better durability, which is due to its unique structural advantages and also reflects the innovative value of high-value utilization of waste resources. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The synthetic C@SiO provided by the present invention x / Process roadmap of MoSe2@CS materials;
[0031] Figure 2 CS, C@SiO x SEM images of @CS and C@MoSe2@CS;
[0032] Figure 3 C@SiO x @CS material spectrum and element distribution map;
[0033] Figure 4 Spectrum and element distribution diagram of C@MoSe2@CS material;
[0034] Figure 5 The C@SiO prepared in Examples 1-4 x SEM image of / MoSe2@CS material;
[0035] Figure 6 C@SiO x / Spectrum and element distribution of MoSe2-3:1@CS material;
[0036] Figure 7 C@MoSe2, C@SiO x / MoSe2@C and C@SiO x XRD, Raman and XPS spectra of / MoSe2-3:1@CS materials;
[0037] Figure 8 C@MoSe2, C@MoSe2@CS, C@SiO x / MoSe2-2:1@CS、C@SiO x / MoSe2-3:1@CS and C@SiO x Thermogravimetric analysis of / MoSe2-4:1@CS;
[0038] Figure 9 The battery performance diagram of different groups of materials when used as negative electrode materials for sodium ion batteries;
[0039] Figure 10 C@SiO x Related images and maps of the MoSe2-3:1@CS material when discharged to 0V;
[0040] Figure 11 C@SiO x Related images and maps of the MoSe2-3:1@CS material when charged to a voltage of 1.9V;
[0041] Figure 12 C@MoSe2@CS, C@SiO x @CS two materials at a current of 0.5A-1 Hours (first 5 laps at 0.1Ag -1 )’s charge and discharge curve diagram;
[0042] Figure 13 C@SiO x The change in electrode thickness of / MoSe2-3:1@CS composite material as SIB electrode before and after charge and discharge. DETAILED DESCRIPTION
[0043] The present invention is further described in detail below through specific preferred embodiments, but the present invention is not limited to the following embodiments.
[0044] It should be noted that, unless otherwise specified, all chemical reagents involved in the present invention were purchased through commercial channels.
[0045] Comparative Example 1
[0046] A method for preparing carbon sphere (CS) material comprises the following steps:
[0047] 550 mg of discarded mask protective layer (PP) was cut into pieces and poured into a ceramic ark, placed in a tube furnace, calcined at 800 ° C for 1 h in an argon atmosphere with a heating rate of 5 ° C / min, and then cooled to room temperature to obtain carbon ball (CS) material.
[0048] Comparative Example 2
[0049] A method for preparing a C@MoSe2 heterojunction composite material comprises the following steps:
[0050] S1. Mix 15 mL of ethylene glycol and 27.2 mg of MoCl5, and then ultrasonicate for 4 h to obtain a dispersion.
[0051] S2. Pour the above dispersion into a ceramic ark containing 24 mg of selenium powder, place it in a tube furnace, and calcine it at 800°C for 1 hour in an argon atmosphere with a heating rate of 5°C / min. Then cool it to room temperature to obtain a C@MoSe2 heterojunction composite material.
[0052] Comparative Example 3
[0053] A method for preparing a C@MoSe2@CS heterojunction composite material comprises the following steps:
[0054] S1. Mix 15 mL of ethylene glycol and 27.2 mg of MoCl5, and then ultrasonicate for 4 h to obtain a dispersion.
[0055] S2, then add 550 mg of discarded mask protective layer PP and mix evenly with the above dispersion to obtain a mixed solution;
[0056] S3. Pour the above mixed solution into a ceramic ark containing 24 mg of selenium powder, place it in a tube furnace, and calcine it at 800°C for 1 hour in an argon atmosphere with a heating rate of 5°C / min. Then cool it to room temperature to obtain a C@MoSe2@CS heterojunction composite material.
[0057] Comparative Example 4
[0058] A C@SiO x The preparation method of the @CS heterojunction composite material comprises the following steps:
[0059] S1. Mix 15 mL of ethylene glycol and 88.2 mg of triphenylsilyl chloride, and then ultrasonicate for 4 h to obtain a dispersion.
[0060] S2, then add 550 mg of discarded mask protective layer PP and mix evenly with the above dispersion to obtain a mixed solution;
[0061] S3. Pour the mixed solution into a ceramic ark, place it in a tube furnace, and calcine it at 800 °C for 1 h in an argon atmosphere at a heating rate of 5 °C / min, and then cool it to room temperature to obtain C@SiO x @CS heterojunction composite material.
[0062] Comparative Example 5
[0063] A C@SiO x The preparation method of the / MoSe2@C heterojunction composite material comprises the following steps:
[0064] S1. Dissolve 27.2 mg of molybdenum pentachloride in 5.6 mL of ethylene glycol to form a molybdenum-based metal organic complex, and then add 88.2 mg of triphenylsilyl chloride and 17 mL of ethylene glycol to obtain a Si-Mo organometallic compound solution;
[0065] S2, ultrasonicating the above solution for 4 hours to obtain a dispersion;
[0066] S3. The above dispersion was poured into a ceramic ark containing 24 mg of selenium powder, placed in a tube furnace, and calcined at 800 ° C for 1 h in an argon atmosphere with a heating rate of 5 ° C / min; then cooled to room temperature. After ultrasonication and calcination, the Mo element in the precursor dispersion was in situ selenized to MoSe2, the organosilicon was oxidized to silicon oxide, and the organic component was in situ converted to carbon material, finally generating C@SiO x / MoSe2@C heterojunction composite material.
[0067] Example 1
[0068] A C@SiO2 synthesized from waste plastic-derived carbon x The preparation method of / MoSe2@CS material includes the following steps:
[0069] S1. First, 27.2 mg of molybdenum pentachloride was dissolved in 5.6 mL of ethylene glycol to form a molybdenum-based metal organic complex, and then 29.4 mg of triphenylsilyl chloride and 17 mL of ethylene glycol were added and ultrasonically dissolved. The molar ratio of triphenylsilyl chloride to molybdenum pentachloride was 1:1 to obtain a Si-Mo organometallic compound solution.
[0070] S2, then mixing the above solution with 550 mg of discarded mask protective layer PP to obtain a mixture;
[0071] S3, then pouring the mixture into a ceramic ark filled with 24 mg of selenium powder, placing it in a tube furnace, calcining it at 800°C for 1 h under an argon atmosphere at a heating rate of 5°C / min, and then cooling it to room temperature;
[0072] After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, the organic silicon is oxidized to silicon oxide, the PP protective layer of the discarded mask is carbonized to carbon balls (CS), and the organic components are in situ converted into carbon materials, finally generating C@SiO x / MoSe2@CS composite material, denoted as C@SiO x / MoSe2-1:1@CS.
[0073] Example 2
[0074] A C@SiO2 synthesized from waste plastic-derived carbon x The preparation method of / MoSe2@CS material includes the following steps:
[0075] S1. First, 27.2 mg of molybdenum pentachloride was dissolved in 5.6 mL of ethylene glycol to form a molybdenum-based metal organic complex, and then 58.8 mg of triphenylsilyl chloride and 17 mL of ethylene glycol were added and ultrasonically dissolved. The molar ratio of triphenylsilyl chloride to molybdenum pentachloride was 2:1 to obtain a Si-Mo organometallic compound solution.
[0076] S2, then mixing the above solution with 550 mg of discarded mask protective layer PP to obtain a mixture;
[0077] S3, then pouring the mixture into a ceramic ark filled with 24 mg of selenium powder, placing it in a tube furnace, calcining it at 800°C for 1 h under an argon atmosphere at a heating rate of 5°C / min, and then cooling it to room temperature;
[0078] After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, the organic silicon is oxidized to silicon oxide, the PP protective layer of the discarded mask is carbonized to carbon balls (CS), and the organic components are in situ converted into carbon materials, finally generating C@SiO x / MoSe2@CS composite material, denoted as C@SiO x / MoSe2-2:1@CS.
[0079] Example 3
[0080] A C@SiO2 synthesized from waste plastic-derived carbon x The preparation method of / MoSe2@CS material includes the following steps:
[0081] S1. First, 27.2 mg of molybdenum pentachloride was dissolved in 5.6 mL of ethylene glycol to form a molybdenum-based metal organic complex, and then 88.2 mg of triphenylsilyl chloride and 17 mL of ethylene glycol were added and ultrasonically dissolved. The molar ratio of triphenylsilyl chloride to molybdenum pentachloride was 3:1 to obtain a Si-Mo organometallic compound solution.
[0082] S2, then mixing the above solution with 550 mg of discarded mask protective layer PP to obtain a mixture;
[0083] S3, then pouring the mixture into a ceramic ark filled with 24 mg of selenium powder, placing it in a tube furnace, calcining it at 800°C for 1 h under an argon atmosphere at a heating rate of 5°C / min, and then cooling it to room temperature;
[0084] After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, the organic silicon is oxidized to silicon oxide, the PP protective layer of the discarded mask is carbonized to carbon balls (CS), and the organic components are in situ converted into carbon materials, finally generating C@SiO x / MoSe2@CS composite material, denoted as C@SiO x / MoSe2-3:1@CS.
[0085] Example 4
[0086] A C@SiO2 synthesized from waste plastic-derived carbon x The preparation method of / MoSe2@CS material includes the following steps:
[0087] S1. First, 27.2 mg of molybdenum pentachloride was dissolved in 5.6 mL of ethylene glycol to form a molybdenum-based metal organic complex, and then 117.6 mg of triphenylsilyl chloride and 17 mL of ethylene glycol were added and ultrasonically dissolved. The molar ratio of triphenylsilyl chloride to molybdenum pentachloride was 4:1 to obtain a Si-Mo organometallic compound solution.
[0088] S2, then mixing the above solution with 550 mg of discarded mask protective layer PP to obtain a mixture;
[0089] S3, then pouring the mixture into a ceramic ark filled with 24 mg of selenium powder, placing it in a tube furnace, calcining it at 800°C for 1 h under an argon atmosphere at a heating rate of 5°C / min, and then cooling it to room temperature;
[0090] After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, the organic silicon is oxidized to silicon oxide, the PP protective layer of the discarded mask is carbonized to carbon balls (CS), and the organic components are in situ converted into carbon materials, finally generating C@SiO x / MoSe2@CS composite material, denoted as C@SiO x / MoSe2-4:1@CS.
[0091] Example 5
[0092] A C@SiO2 synthesized from waste plastic-derived carbon x The preparation method of / MoSe2@CS material includes the following steps:
[0093] S1. First, 27.2 mg of molybdenum pentachloride was dissolved in 5.6 mL of ethylene glycol to form a molybdenum-based metal organic complex, and then 147 mg of triphenylsilyl chloride and 17 mL of ethylene glycol were added and ultrasonically dissolved. The molar ratio of triphenylsilyl chloride to molybdenum pentachloride was 5:1 to obtain a Si-Mo organometallic compound solution.
[0094] S2, then mixing the above solution with 550 mg of discarded mask protective layer PP to obtain a mixture;
[0095] S3, then pouring the mixture into a ceramic ark filled with 24 mg of selenium powder, placing it in a tube furnace, calcining it at 800°C for 1 h under an argon atmosphere at a heating rate of 5°C / min, and then cooling it to room temperature;
[0096] After ultrasonic and calcination reactions, the Mo element in the precursor dispersion is in situ selenized to MoSe2, the organic silicon is oxidized to silicon oxide, the PP protective layer of the discarded mask is carbonized to carbon balls (CS), and the organic components are in situ converted into carbon materials, finally generating C@SiO x / MoSe2@CS composite material, denoted as C@SiO x / MoSe2-5:1@CS.
[0097] In the embodiment of the present invention, C@SiO2 is synthesized based on waste plastic-derived carbon. x / The process roadmap of MoSe2@CS material is as follows Figure 1 shown.
[0098] The materials prepared in the examples and comparative examples of the present invention were characterized as follows:
[0099] By using SEM and TEM techniques, CS, C@SiO x The structures of @CS and C@MoSe2@CS were characterized. Figure 2 As shown, Figure 2 The ac in the middle is the SEM image of CS material. It can be observed that there are many carbon spheres of different sizes and similar shapes in the SEM image of CS material. These carbon spheres (CS) are the subsequent SiO x and MoSe2 provide growth templates; Figure 2 Where df is C@SiO x @SEM image of CS material, Figure 2 The SEM images of C@MoSe2@CS materials are shown in the figure. x From the SEM images of C@CS(df) and C@MoSe2@CS(gi), it can be seen that when SiO x or MoSe2, it still maintains a spherical morphology and a regular shape, and no morphology other than spherical appears, proving that SiO x Both MoSe2 and MoSe2 grow along the surface of carbon spheres (CS) and are evenly distributed, making full use of the active sites on the surface of carbon spheres (CS).
[0100] Figure 3 C@SiO x TEM images of @CS materials, from Figure 3 The EDS element analysis of (df) shows three elements: C, O, and Si. The three elements are evenly distributed. From the aggregation of O and Si, it can be inferred that SiO x Successfully formed and evenly attached to the carbon spheres.
[0101] Figure 4 This is the TEM image of C@MoSe2@CS material. EDS elemental analysis shows the uniform distribution of C, Se, and Mo. The overlapping part of Se and Mo elements also proves the existence of MoSe2 and its growth around the surface of carbon spheres. Figure 4 In figure a, it can be observed that the lattice interlayer spacing is about 0.65 nm, which corresponds to the (002) crystal plane of MoSe2, and also confirms the formation of MoSe2 nanosheets.
[0102] Figure 5 The C@SiO prepared in Examples 1-4 x / MoSe2@CS material SEM images, where ac is the SEM image of the material prepared in Example 1, df is the SEM image of the material prepared in Example 2, gi is the SEM image of the material prepared in Example 3, and jl is the SEM image of the material prepared in Example 4. In these four groups of images, different forms of carbon spheres can be seen. By comparing the four groups of images, it can be found that there are many blocky particles in Figures (ac), (df) and (df). The presence of this morphology is not conducive to the dispersion of active materials, which reduces the performance of sodium ion batteries. However, in Figure (gi), not only is there no blocky morphology, but the carbon spheres are of uniform size, which promotes the dispersion of MoSe2 nanosheets and SiO x The dispersion of particles improves the mobility of sodium ions. Therefore, we choose the molar ratio of triphenylsilane and molybdenum pentachloride to be 3:1 as the optimal ratio.
[0103] Figure 6 The C@SiO prepared in Example 3 x TEM image of / MoSe2@CS material, Figure 6 The lattice interlayer spacing of b is about 0.65nm, which matches the (002) crystal plane of MoSe2, proving that the MoSe2 nanosheets are grown on the carbon spheres. The few-layer MoSe2 nanosheets grow around the carbon spheres and produce local bending due to stress and interface interaction, which not only provides Na + The embedding provides a good channel and improves the Na + It not only increases the storage capacity of silicon, but also plays the role of dispersing and storing silicon, thereby improving the performance of the battery; and it can be observed that the outermost layer is also wrapped by amorphous carbon, which helps to reduce the volume expansion during charging and discharging. Figure 6 In the element distribution diagram of (di), Mo and Se elements completely overlap, which once again confirms the formation of MoSe2. At the same time, the dispersion of Si and O elements verifies the formation of SiO x / MoSe2 composite structure.
[0104] In order to further verify the characteristics of the materials, C@MoSe2, C@SiO x / MoSe2@C and C@SiO prepared in Example 3 x The / MoSe2@CS material was subjected to XRD, Raman and XPS analysis. Figure 7 As shown, Figure 7 Middle a shows C@MoSe2 material, C@SiO x / MoSe2@C materials and C@SiO x XRD patterns of C@SiO / MoSe2@CS materials in the range of 10 to 80 (2θ). x / MoSe2@C and C@SiO x The peak of / MoSe2@CS at 26.2° corresponds to the (011) crystal plane of SiO2 (JCPDS 47-1144), while the peaks at 47° and 56° correspond to SiO (JCPDS 30-1127); in addition to these peaks, the other peaks correspond to the peak group of MoSe2 (JCPDS29-0914), indicating the large-scale formation of MoSe2.
[0105] Figure 7 (bd) show C@MoSe2 material, CS material, C@SiO x / MoSe2@C materials and C@SiO x Raman spectrum of / MoSe2@CS material. Figure 7 As shown in b, 238.0cm -1 Represents the out-of-plane atomic vibration mode of Mo-Se (A 1g ), 283.1cm -1 Representing the in-plane atomic vibration mode of Mo-Se It can be seen that C@MoSe2(12.29), C@SiO x / MoSe2@C(1.08) and C@SiO x / MoSe2@CS(3.41) from A 1g arrive The intensity ratio of SiO x and carbon sphere (CS) substrate have a certain influence on the structure of MoSe2. Figure 7 As shown in middle d, C@MoSe2, CS, C@SiO x / MoSe2@C and C@SiO x The Raman spectrum of / MoSe2@CS shows that 1352 cm -1 and 1586cm -1 The two peaks at the center correspond to the D peak and the G peak, respectively. The D / G intensity ratios are C@MoSe2 (0.91), CS (1.03), C@SiO x / MoSe2@C(0.96) and C@SiO x / MoSe2@CS(0.98), it can be seen that C@MoSe2, CS, C@SiO x / MoSe2@C and C@SiO x The intensity ratios of / MoSe2@CS are almost the same, demonstrating that they have similar defects and graphitization degrees.
[0106] XPS technology can be used to analyze the C@SiO prepared in Example 3. x / MoSe2@CS composite surface element composition and oxidation state. In the full spectrum ( Figure 7 In e), the signals of O, Mo, C, Se and Si elements can be observed. Figure 7 In the Mo3d spectrum (C 1s spectrum), there are three main peaks located at 289.2eV, 286.3eV and 28 8eV, corresponding to C=O, CO and CC bonds. Figure 7 In g), Mo 3d is observed at 232.2 eV. 3 / 2 signal, Mo 3d was observed at 229eV 5 / 2 Signal indicating that Mo 4+ The existence of Figure 7 h (Se 3d spectrum), Se 3d was observed at 55.8 eV 3 / 2 signal, Se 3d was observed at 56 eV 5 / 2 Signal, indicating Se 2+ The presence of. In the Si 2p spectrum ( Figure 7 In i), the signals at 103.6 eV and 102.1 eV correspond to tetravalent and divalent silicon, respectively, confirming the formation of SiO2 and SiO.
[0107] Figure 8 C@MoSe2 (Comparative Example 2), C@MoSe2@CS (Comparative Example 3), C@SiO x / MoSe2-2:1@CS (Example 2), C@SiO x / MoSe2-3:1@CS (Example 3) and C@SiO x / MoSe2-4:1@CS (Example 4) thermogravimetric analysis diagram; Thermogravimetric analysis (TGA) can be used to determine the x MoSe2 and SiO in MoSe2-2 / 3 / 4:1@CS x When heated in air, SiO x When completely converted into SiO2, its weight change is negligible, while MoSe2 will oxidize to form MoO3 and SeO2 before 350℃, so there will be a weight gain phenomenon. After that, there will be two stages of weight loss. The weight loss in the first stage is due to the sublimation of SeO2, and the weight loss in the second stage is due to the oxidation of carbon. At the temperature of 900-1000℃, the residual contents of C@MoSe2 and C@MoSe2@CS are 2.2% and 8.5% respectively, and the residue is MoO3. C@SiO x / MoSe2-2:1@CS、C@SiO x / MoSe2-3:1@CS and C@SiO x / MoSe2-4:1@CS in SiO x The contents of iodine and nitrate were 7.8%, 10.7% and 20.9% respectively.
[0108] According to the Mo element conservation rule, the proportion of MoSe2 can be calculated using formula (1):
[0109]
[0110] in is the molecular weight of MoSe2, is the molecular weight of MoO3; is the mass percentage of MoSe2 in the composite material, is the mass percentage of MoO3 in the composite material (400-600℃). Specifically, C@MoSe2, C@MoSe2@CS, C@SiO x / MoSe2-2:1@CS、C@SiO x / MoSe2-3:1@CS and C@SiO x / MoSe2-4:1@CS The C@MoSe2 material, C@MoSe2@CS material, C@SiO x / MoSe2-2:1@CS materials, C@SiO x / MoSe2-3:1@CS materials and C@SiO x The MoSe2 contents in the / MoSe2-4:1@CS materials were calculated to be 93.6%, 91.18%, 56.7%, 59.8% and 51.3%, respectively.
[0111] The composite materials prepared in the comparative example and the example were mixed with acetylene black and carboxymethyl cellulose (CMC) in a mass ratio of 4:1:1 and ground. The mixture was stirred with water and ethanol as solvents to form a slurry, which was then evenly coated on copper foil to make electrode materials. The energy storage performance of sodium ion batteries (SIBs) with the three negative electrode materials was tested by making button batteries. The results are as follows: Figure 9 shown.
[0112] Figure 9 Figure a shows C@SiO x Cyclic voltammetry (CV) curves of the / MoSe2-3:1@CS composite as a SIB electrode. In the initial CV scan, three cathodic peaks were noted at 1.94 V, 0.62 V, and 0.35 V. The peak (1.94 V) represents the Na + Insertion into MoSe2 to form Na xMoSe2, then Na x The process of MoSe2 conversion to Mo and Na2Se. The peaks (0.62V and 0.35V) represent the alloying of amorphous silicon and the formation of the solid electrolyte interface (SEI) layer, respectively. In addition, two anodic peaks appeared at 1.72V and 2.0V during the charging process. The peak (1.72V) represents the partial oxidation of metallic Mo to MoSe2 and the partial conversion of Na2Se to Se. At the same time, the peak (2.0V) is due to the dealloying of silicon.
[0113] Figure 9 Figure b shows the material C@SiO x Galvanostatic charge-discharge curves of / MoSe2-3:1@CS as SIB electrode (0.1Ag -1 ), the first discharge and charge capacities are 1675.33mAh g -1 and 853.73mAh g -1 (with a charge-discharge efficiency of 51%), the initial charge-discharge efficiency is low, which may be attributed to the formation of the SEI layer in the first cycle, which also leads to the first high irreversible capacity.
[0114] Figure 9 c is the C@SiO prepared in Example 1-5 x The battery performance diagram of MoSe2@CS material as the negative electrode material of sodium ion battery shows that the SiO x When the ratio of triphenylsilane to molybdenum pentachloride is 3:1, the cycling performance is the best, with the highest initial discharge capacity (1609 mAh g -1 ), and after 300 cycles, the capacity is still 6481mAh g -1 After 500 cycles, it still maintains at 548.15 mAh g -1 High discharge capacity. Research has confirmed that high capacity SiO x Combined with two-dimensional MoSe2, it effectively enhances the energy density and cycle life of the battery.
[0115] Figure 9 Middle d shows C@SiO x / MoSe2-3:1@CS rate performance, when the current density increases from 0.1 to 10A -1 When the charge and discharge specific capacity is gradually reduced, it can be observed that the charge and discharge specific capacity gradually decreases. -1 In the case of , the corresponding average discharge specific capacities are 1102, 862, 748, 663, 632, 583, 546, 493, 454, 425 and 333 mAh g-1 After undergoing high current cycling, the material -1 Still can return to 932mAh g -1 The reversible capacity of the electrode was confirmed to be stable.
[0116] Figure 9 Zhonge shows C@SiO x The long cycle performance of / MoSe2-3:1@CS is shown in Figure 2. -1 ), it still maintains 387.53mAh g -1 Even after 5000 cycles, the capacity is still maintained at 355.64 mAh g -1 , showing excellent cycle life. C@SiO x The excellent performance of the MoSe2-3:1@CS composite material is due to its three-layer composite structure. The nano-scale carbon spheres are structurally stable during the cycle, and the two-dimensional MoSe2 nanosheets not only play the role of dispersed storage of silicon but also can alleviate the volume change caused by silicon oxide. In addition, the carbon layer's coating protection constructs a stable electrode / electrolyte interface, inhibits the formation of thick SEI films, and successfully improves the battery's cycle performance and specific capacity.
[0117] Figure 10 The C@SiO prepared in Example 3 x Related images and maps of the C@SiO / MoSe2-3:1@CS material when discharged to a voltage of 0V, including (a) HRTEM image; (b) STEM image; (c) element distribution; (di) EDS element map; x Ex situ transmission electron microscopy (TEM) images of / MoSe2-3:1@CS ( Figure 10 As can be seen in a), when discharged to 0V, sodium ions are inserted into the NaSe2 lattice formed in MoSe2, and the interlayer spacing matches the NaSe2 (200) crystal plane, which is about 0.34nm. In addition, Figure 10 The positions where Na and Se elements are concentrated in f and h coincide, which also proves the existence of NaSe2.
[0118] Figure 11 The C@SiO prepared in Example 3 x Related images and maps of the / MoSe2-3:1@CS material when charged to 1.9V, including (a) HRTEM image; (b) STEM image; (c) element distribution; (di) EDS element map; When charged to 1.9V, it can be seen from the non-in situ transmission electron microscopy (TEM) image ( Figure 11In a), a lattice with an interlayer spacing of about 0.65 nm is seen, corresponding to the (002) crystal plane of MoSe2. At this time, sodium ions are embedded from the negative electrode material, which matches the CV image. Starting from the second cycle, the main cathode peaks at 1.38 V and 1.95 V are due to Na + The CV curves are almost overlapped since the second cycle, indicating the stability of the material during charge and discharge.
[0119] Figure 12 C@MoSe2@CS (Comparative Example 3), C@SiO x @CS (Comparative Example 4) The two materials were tested at a current of 0.5A. -1 Hours (first 5 laps at 0.1Ag -1 ), among which C@MoSe2@CS has a higher initial discharge capacity of 1358.64mAh g -1 , and after 300 cycles, it still maintains 359.73mAh g -1 Discharge specific capacity; and C@SiO x @CS’s charge and discharge capacity is relatively low, and its initial discharge capacity is only 588.55 mAh g -1 After 300 cycles, it is only 146.91 mAh g -1 , indicating that silicon oxide cannot well demonstrate its high theoretical capacity on a single carbon sphere. Therefore, MoSe2 nanosheets were introduced, and many MoSe2 nanosheets grew on carbon spheres as SiO x It provides a specific growth space and plays an excellent dispersing role.
[0120] Figure 13 The C@SiO prepared in Example 3 x The thickness change of the electrode sheet before and after charge and discharge of the C@SiO composite material as a SIB electrode. x The morphology of / MoSe2-3:1@CS remained stable after charge and discharge, and the thickness of the electrode sheet increased from 18.6μm to 22.8μm on average, without significant structural collapse. This proves that C@SiO x / MoSe2-3:1@CS has carbon sphere (CS) as the core, SiO x The unique three-layer structure of MoSe2 as the middle layer and carbon layer (C) as the coating layer buffers the volume change during charge and discharge, thereby improving the C@SiO x Stability of / MoSe2-3:1@CS composite material and its long cycling performance as SIB electrode material.
[0121] The present invention uses waste plastic PP as a carbon source to synthesize a new three-layer spherical composite material C@SiO x / MoSe2@CS. The composite material consists of a carbon ball core (CS), an intermediate layer of SiO x / MoSe2 and an outer protective carbon layer (C). The carbon spheres as the core make the MoSe2 nanosheets uniformly dispersed, which not only provides a large sodium storage capacity but also provides a high capacity SiO x The uniform dispersion of particles provides sites to avoid SiO x The aggregation of particles improves the capacity retention rate. In addition, the amorphous carbon layer acts as a strong framework to not only x / MoSe2 volume expansion, and avoid the formation of thick SEI film. Thanks to these advantages, the composite material C@SiO x / MoSe2@CS has excellent cycling stability and electrochemical performance. When used as a negative electrode for sodium-ion batteries, it exhibits excellent sodium storage performance: at 0.5Ag -1 Under the condition of high-pressure ionization, the discharge capacity after 300 and 500 cycles is 64 81 mAh g -1 and 548.15mAh g -1 Even at 5Ag -1 At a high current density of 1.57 Å, the capacity of the battery remained at 387.53 mAh g after 3000 and 5000 cycles, respectively. -1 and 355.64mAh g -1 The present invention not only develops a high-performance SIBs anode material, but also provides an economical and environmentally friendly way to recycle waste plastics. It also proves the feasibility of converting waste into high-value-added materials, provides new ideas for the development of sustainable energy storage technology, and helps to design more environmentally friendly sodium-ion battery anode materials.
[0122] Finally, it should be noted that the above embodiments do not limit the present invention in any form. Those skilled in the art will appreciate that modifications and improvements can be made based on the present invention. Therefore, any modifications or improvements made without departing from the spirit of the present invention are intended to fall within the scope of protection claimed in the present invention.
Claims
1. A C@SiO2 synthesized from waste plastic-derived carbon x The preparation method of / MoSe2@CS material is characterized in that: The steps include: S1, dissolving molybdenum pentachloride in ethylene glycol solution A, then adding triphenylsilyl chloride and ethylene glycol solution B to obtain a Si-Mo organometallic compound solution; S2, adding the discarded mask protective layer to the Si-Mo organometallic compound solution, mixing evenly to obtain a mixture; S3, pouring the above mixture into a ceramic ark filled with selenium powder, placing the ceramic ark in a tube furnace, and calcining it under an inert atmosphere to obtain C@SiO x / MoSe2@CS material.
2. The preparation method according to claim 1, characterized in that In step S1, the molar ratio of molybdenum pentachloride to triphenylchlorosilane is 1:1-5.
3. The preparation method according to claim 1, characterized in that In step S1, the volume ratio of ethylene glycol solution A to ethylene glycol solution B is 1:3-5.
4. The preparation method according to claim 1, characterized in that The mass ratio of molybdenum pentachloride, discarded mask protective layer and selenium is 1:10-30:0.5-2.
5. The preparation method according to claim 1, characterized in that In step S2, the material of the protective layer of the discarded mask is polypropylene.
6. The preparation method according to claim 1, characterized in that In step S3, the inert atmosphere is nitrogen or argon.
7. The preparation method according to claim 1, characterized in that In step S3, the calcination temperature is 750-900° C., the calcination time is 1-2 hours, and the heating rate is 5-10° C. / min.
8. C@SiO synthesized from waste plastic-derived carbon prepared by the preparation method according to any one of claims 1 to 7 x / MoSe2@CS material.
9. The C@SiO2 synthesized based on waste plastic-derived carbon according to claim 8 x Application of / MoSe2@CS materials in electrode materials.
Citation Information
Patent Citations
Synthesis method and application of C-coated SiOx / MoSe2-coated NMWCNT material constructed based on NMWCNT
CN118867192A